Local decarbonisation opportunities and barriers: UK public procurement legislation. Issue 1 (11th November 2022) - Sugar, Katherine; Mose, Tedd Moya; Nolden, Colin; Davis, Mark; Eyre, Nick; Sanchez-Graells, Albert; Van der Horst, Dan
Significant changes in public procurement are underway in the UK. Post-Brexit, the UK government is in the process of modifying the procurement rulebook. The new regime will be guided by the procurement strategy priorities of social value, jobs and net zero; however, the new approach to procurement foresees minimal rules and significant guidance. This paper explores implications of changing procurement legislation on the delivery of net zero at a local level in the UK. Particular focus lies on the many contracting authorities, such as county, city and district councils, that have declared climate emergencies and ambitions to decarbonise. Two case studies depicting the procurement of local net zero solutions, one on the Energy Efficient Scotland Programme and the other on place-based finance instruments, such as community municipal investments (CMIs), are used to identify existing opportunities and barriers to procure local net zero solutions with a particular focus on institutional governance. This paper concludes with a set of questions that need to be addressed to ensure that the changes to public procurement legislation are understood and that the institutional governance of intermediation can lead to outcomes that balance economic, social and environmental considerations across multiple scales. Practice relevance: The absence of a rich approach to multilevel governance in the UK means that procurement is one of the few options currently available to many local authorities to deliver net zero at the local level. Given the scale of investments necessary to reach net zero, institutional governance is necessary to align top-down procurement and bottom-up finance with many other laws, policies and regulations. This paper explores the implications of changing procurement legislation on the delivery of net zero at a local level. Two case studies depicting the procurement of local net zero solutions (the Energy Efficient Scotland Programme and place-based finance instruments, e.g . CMIs) are used to identify existing opportunities and barriers to procure local net zero solutions. Guidance on understanding public procurement legislation is provided to ensure that the institutional governance of intermediation can lead to outcomes that balance economic, social and environmental considerations (especially decarbonisation) across multiple scales.